Sleep Quality Among Pre-Service Teachers: The Role of Academic Stress and Time Management - Siti Muthia Dinni; Ardelia Arista Putri (HUMANITAS published by Universitas Ahmad Dahlan., 2026)
Sleep quality is essential for university students, as it affects cognitive functioning, concentration, and academic performance. Poor sleep may increase vulnerability to psychological distress, particularly among students enrolled in academically demanding programs. This study examined the roles of academic stress and time management in predicting sleep quality among pre-service teacher professional education (PPG) students. A total of 142 students from a private university in Yogyakarta, Indonesia, participated in this study. Data were collected through Sleep Quality, Time management and Academic stress Scales and were analysed using multiple linear regression. The results indicated that academic stress and time management jointly predicted sleep quality (F= 13.80, p< .001), accounting for 16.54% of the variance. Higher academic stress was associated with poorer sleep quality, whereas better time management was associated with better sleep quality. Academic stress emerged as the stronger predictor. These results highlight the importance of stress management and time regulation skills in supporting sleep health among pre-service teachers. Interventions targeting academic stress reduction and effective time management may contribute to improved well-being and academic functioning.